NILAI-NILAI PENDIDIKAN DALAM AL-QUR’AN PERSPEKTIF LINGUISTIK - Fahrul Usmi (Program Studi Ilmu Al-Qur’an dan Tafsir Fak. Ilmu Agama Islam Universitas Islam Indragiri, 2020)
From a linguistic perspective, the Qur'an has a very beautiful and balanced composition of words and phrases. The beauty of the language is a miracle in itself for this holy book. If it is explored and analyzed in depth using its knowledge, it will find a variety of useful values from the aspect of the language referred to. Among the values that can be expressed are educational values. When the Qur’an as holy book chooses the pronoun and indicative word used, linguistically it is not a coincidence, but deliberately said by the Almighty God like that. For example, when God told about Adam in heaven, 1). Allah told Adam to stay in heaven and please enjoy all the facilities, but don't even ever approach this tree. 20 utterances. Allah said to Adam when His prohibition was violated by Adam because of being consumed by the seduction of the devil, Allah said;